Study on bearing strength of fiber reinforced polymer anchoring cable in deep roadway - Lei Wang; Yilin Wu; Dongmei Chen; Wei Lu; Huibin Sun; Yongzheng He; Kunpeng Liu; Yiwen Zhang (Scientific Reports)
Abstract Roof-cutting and roadway retaining (RCRR) technology refers to the process of mining a coal mine face without retaining protective coal pillars. By cutting the roof, the previous section of the transportation roadway is retained as the track roadway for the next section, which has the advantages of good economic value and fast construction speed. The most important factor of RCRR effectiveness lies in the stability of the retained roadway roof, especially in areas with complex geological conditions. Due to high ground stress, ground water pressure and weak surrounding rock, the roof stabilizing and bearing mechanism is complex, restricting the promotion of RCRR. In response to above difficulties, the fiber reinforced polymer (FRP) anchoring cable is introduced for the roof stability control owing to its high strength and low costs. In this paper, the calculation formula of the bearing strength of the Fiber reinforced polymer anchoring cable in the top cutting and retaining roadway is derived. We have also discussed the effects of various strength properties of the FRP anchoring cable, including cohesion, internal friction angle, and preload, as well as layout parameters such as cable spacing, length, and diameter. The results indicate that as the strength parameters, preload, length, and diameter of FRP anchoring cable increase, so does the bearing strength of the FRP anchoring cable in the roadway. Therefore, using high-strength and high preload FRP anchoring cables with grouting reinforcement can effectively ensure the stability of the retained roadway roof. The research results can provide theoretical and practical experience for relevant engineering cases.